Analisis Pertumbuhan Tanaman Restorasi di Taman Nasional Matalawa - Suyogia Nur Azis; Nurheni Wijayanto; Arum Sekar Wulandari (Jurnal Silvikultur Tropika, 2020)
Ecosystem restoration in Matalawa National Park is an effort to restore the condition of the forest so as to achieve the function of forest to maintain biodiversity. This research aims to analyze the biophysical influence against growth of plant restoration. The research was conducted in Manurara, Taman Mas, Tangairi and Waimanu. The object of the research consists of adinu plant (Melochia umbellata), cimung plant (Timonius timon), kihi plant (Canarium acutifolium), langaha plant (Planchonia valida) and mara plant (Tetrameles nudiflora). The experiment was analyzed by pearson correlation coefficient (r) and t test. The results showed biophysical environmental factors have a very strong relationship with the growth of restoration plants in Matalawa National Park is phosphorus, CEC, pH and altitude of site. Besides, the growth of adinu plant is higher than other plants in open area conditions. Keywords: biophysical, characteristics of plant species, forest restoration, national park